Masculinization of Mutiara’s Catfish (Clarias gariepinus) Using Cow’s Testicles Flour Through Immersion Technique - Ringo Ringo Star Osrin, Butet Mona Moranaga; Iskandar; Junianto; Irfan Zidni (Universitas Islam Lamongan, 2025)
The production of male catfish is faster, resulting in a shorter harvest period, which can increase profits for farmers. To produce superior male catfish fry, masculinization is conducted. Cow's Testicles Flour (CTF) is one of the natural alternative materials that can be used for the masculinization process in fish. This study aims to determine the best concentration of cow's testicles flour to enhance the success of masculinization in mutiara’s catfish (Clarias gariepinus) through immersion techniques. The method used is an experimental method consisting of 4 treatments with 4 replicates (0 mgL⁻¹, 45 mgL⁻¹, 60 mgL⁻¹, and 75 mgL⁻¹ CTF). The parameters observed were the percentage of male sex, survival rate, growth, and water quality. The highest percentage of male catfish was obtained at a concentration of 60 mgL⁻¹ CTF, at 72%. The highest absolute length and specific length growth rate were found at the 60 mgL⁻¹ CTF dosage, measuring 5.43 cm and a specific length growth rate of 3.05%. The highest absolute weight in catfish was found at the 75 mgL⁻¹ CTF dosage, at 4.69 g. The highest specific weight growth rate in catfish was observed in the control treatment, at 2.40%. The ideal water quality to support the survival of catfish includes a temperature range of 26.26-29.85°C; pH range of 6.5-8.3; and DO range of 4.6-6.7 mgL⁻¹.